Apuntes acerca de la responsabilidad solidaria en el Impuesto a la Renta de la sociedad emisora en la enajenación directa de acciones directas realizada entre partes no vinculadas - Vega-León Cabrera, Sergio (2021)
Through this essay, the author comments on the problems derived from the several liability that, under certain circumstances, the share issuing company acquires within the framework of a share transfer. For such purposes, the author addresses the scope of article 68 of the Income Tax Law, as well as its origins and the most relevant precedents, to later make brief reflections on this topic.